The legitimacy of global accounting rules: a note on the challenges from path-dependence theory - Esther Pittroff (Journal of Management and Governance, 2020)
This paper discusses the legitimacy of the convergence of accounting regulation from the view of path-dependence theory. It is argued here that legitimacy of converged accounting rules is almost impossible to achieve because of the path-dependent development of corporate governance systems, which depends on the prevailing norms and beliefs of society. The different elements of corporate governance systems have to be consistent with these values in order to achieve the real convergence of accounting standards. The paper analyses the development of accounting convergence and discusses different convergence strategies from the view of legitimacy theory and path-dependence theory. Finally, the paper presents a hypothetical solution under which real convergence of accounting standards seems possible. The results of the paper are relevant for accounting research, and important to regulators as well, because, by analysing the factors that influence convergence, the paper is able to help us to understand why real convergence of accounting regulation may be difficult to achieve.
Keywords: K22; M41; M48; 650; Accounting regulation; Path-dependence theory; Legitimacy; Corporate governance systems; Convergence; Standard-setting; IFRS